THE OBTAINING OF THE RECOMBINANT CAMEL CHYMOSIN BY SUBMERGE FERMENTATION IN THE PILOT BIOREACTOR - Akishev, Zh.; Abdullayeva , A.; Mussakhmetov, A.; Bekbayeva , A.; Tursunbekova , A.; Kalemshariv , B.; Tultabayeva , T.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2023)
In the cheese making industry, chymosin is used as a milk-clotting enzyme. With its high specific activity against κ-casein, chymosin better than other proteolytic enzymes. Bactrian camel chymosin has a milk-clotting activity higher than calf chymosin. A scheme for obtaining a milk-clotting preparation based on recombinant camel chymosin is proposed. Submerge fermentation of recombinant yeast Pichia pastoris was carried out in a 50-liter bioreactor and recombinant camel chymosin was obtained. The activity of chymosin in the yeast culture was 174.5 U/mL. Chymosin was concentrated 5.6-fold by cross-flow ultrafiltration with 10 kDa cut-off membrane, and chymosin was purified by ion exchange chromatography. The activity of purified chymosin was 4700 U/mL. By sublimation drying with casein peptone, the powder chymosin was obtained with an activity of 36,000 U/g. The proposed scheme for obtaining a milk-clotting drug based on recombinant camel chymosin using submerge fermentation of recombinant yeast has the prospect of being used at biotechnological enterprises.